2011
DOI: 10.1534/genetics.111.130674
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence That Synaptonemal Complex Axial Elements Govern Recombination Pathway Choice in Mice

Abstract: Chiasmata resulting from interhomolog recombination are critical for proper chromosome segregation at meiotic metaphase I, thus preventing aneuploidy and consequent deleterious effects. Recombination in meiosis is driven by programmed induction of double strand breaks (DSBs), and the repair of these breaks occurs primarily by recombination between homologous chromosomes, not sister chromatids. Almost nothing is known about the basis for recombination partner choice in mammals. We addressed this problem using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 101 publications
(153 reference statements)
3
42
0
Order By: Relevance
“…Although mGSCs have been differentiated into spermatogenic cells when they were co-cultured in vitro with feeder layer cells, treated with RA or transplantated in vivo (Feng et al 2002;Kanatsu-Shinohara et al 2003), few reports have shown that murine SSCs are induced in vitro to form haploid male germ cells using RA. Sycp3 and TH2B, specific markers of haploid male germ cells (Lim et al 2010;Li et al 2011), are expressed by haploid male germ cells, as seen in our result. In addition, the result from cell analysis by indirect immunofluorescence demonstrated that haploid male germ cells largely expressed protamine 1 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Although mGSCs have been differentiated into spermatogenic cells when they were co-cultured in vitro with feeder layer cells, treated with RA or transplantated in vivo (Feng et al 2002;Kanatsu-Shinohara et al 2003), few reports have shown that murine SSCs are induced in vitro to form haploid male germ cells using RA. Sycp3 and TH2B, specific markers of haploid male germ cells (Lim et al 2010;Li et al 2011), are expressed by haploid male germ cells, as seen in our result. In addition, the result from cell analysis by indirect immunofluorescence demonstrated that haploid male germ cells largely expressed protamine 1 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely to the situation in mammals, the htp-3 mutant of C. elegans suggests that an AE component might be critical in early recombination initiation in this organism (Goodyer et al 2008). Yet some previous genetic studies in mice proposed that, even though not necessary for DSB formation, AEs function in recombination pathway choice and direct recombination proteins to favor interhomolog rather than intersister recombination repair of DSBs in meiosis (Kouznetsova et al 2011;Li et al 2011). Definitely, DSB formation is required for further steps of homolog pairing and synapsis in mammals but not in C. elegans and Drosophila where synapsis is DSB-independent (Page and Hawley 2003).…”
Section: First Step: the Assembly Of The Chromosomal Axes And The Aximentioning
confidence: 99%
“…In addition, for a crossover to generate a chiasma, the crossover must occur between homologs and not between sisters. Thus, there appears to be a barrier (or semipermeable barrier) between the sister chromatids that promotes homolog exchange, possibly involving the activity of chromosome axis proteins (Couteau et al 2004;Webber et al 2004;Niu et al 2005;Kim et al 2010;Li et al 2011). Finally, homologous repair must be promoted while more error-prone mechanisms that could introduce de novo mutations in the germline such as nonhomologous end joining (NHEJ) are inhibited.…”
mentioning
confidence: 99%